EasyLearnify - A Student Study Portal - Shreyash, Surajsingh Gaur; Chitra, K.; Noor Zuhaili, Md Yasin (INTI International University, 2024)
EasyLearnify is web-based online research developed using Django framework of Python. Django is a high-level Python web framework that encourages rapid development and clean, pragmatic design. The research is designed to facilitate and enhance student's learning experience. The research mainly provides 8 different features for the students. It consists of Notes, Homework, YouTube, To Do List, Books, Dictionary, Wikipedia and Conversions. The main objective of EasyLearnify is to provide all in one study portal where students can manage all their study related works. The admin can also add and assign task to the students. Admin can upload notes which the students can download and assign homework for the students. Basically, it is a centralized hub for students to access various educational resources.